Economic assessment of high-thrust and solar-sail propulsion for near-earth asteroid mining. Issue 9 (1st May 2021) - Vergaaij, Merel; McInnes, Colin R.; Ceriotti, Matteo
Highlights: Integrating economics into trajectory optimization yields more realistic missions. Asteroid mining can be profitable using both chemical and solar-sail propulsion. Attainable target asteroids should have Earth-like orbits. The attainable target region is larger for solar sails than for chemical propulsion. Abstract: Asteroid mining has the potential to greatly reduce the cost of in-space manufacturing, production of propellant for space transportation and consumables for crewed spacecraft, compared to launching the required resources from the Earth's deep gravity well. This paper discusses the top-level mission architecture and trajectory design for these resource-return missions, comparing high-thrust trajectories with continuous low-thrust solar-sail trajectories. The paper focuses on maximizing the economic Net Present Value, which takes the time-cost of finance into account and therefore balances the returned resource mass and mission duration. The different propulsion methods are compared in terms of maximum economic return and sets of attainable target asteroids. Results for transporting resources to geostationary orbit show that the orbital parameter hyperspace of suitable target asteroids is considerably larger for solar sails, allowing for more flexibility in selecting potential target asteroids. Also, results show that the Net Present Value that can be realized is larger when employing solar sailing instead of chemical propulsion. In addition, it is demonstrated that a higher Net Present Value can be realized when transporting volatiles to the Lunar Gateway instead of geostationary orbit. The paper provides one more step towards making commercial asteroid mining an economically viable reality by integrating trajectory design, propulsion technology and economic modelling.